S03.2 Patterns of recurrent thrombosis in primary antiphospholipid syndrome –multicentre, real life long term follow-up. (27th September 2022) - Niznik, S; Rapoport, M; Avnery, O; Ellis, M; Lubetsky, A; Haj Yahia, S; Agmon-Levin, N
Abstract : Background: Antiphospholipid Syndrome (APS) is an acquired hypercoagulable condition associated with antiphospholipid antibodies (aPLs) presence. Data on re-thrombosis following APS-diagnosis is limited. Methods: Retrospective analysis of new thrombotic events among primary-APS (pAPS) patients followed for up to 15 years in three medical centres in Israel. Results: Among 312 primary-APS patients 143 (46%) had new thrombotic event classified to three patterns: (1) Arterial - associated with heart valve disease (OR 7.24, 95% C.I. 2.26–24.6), hypertension (OR 3, 95% C.I. 1.44–6.25), elevated anti B2-GPI IgM (OR 1.04, 95% C.I. 0.996–1.08), arterial thrombosis at presentation (OR 1.74 CI95% 0.992–3.26) and older age (41 vs. 34 years, p<0.001). (2) Venous – linked with venous thrombosis at presentation (OR 12.9, 95% C.I. 5.27–31.6, p<0.001), heart valve disease (OR 9.81 CI95% 1.82–52.9, p=0.018), aGAPSS (OR 1.15 CI95% 1.02–1.29) and younger age (31 vs. 36.5 years, p=0.001); (3) Combined pattern - associated with heart valve disease (OR 40.5 95% C.I. 7.7- 212) and pulmonary embolism (OR 7.47 95% C.I. 1.96–28.5). A 4th variant 'the Breakthrough pattern' defined by re-thrombosis despite prophylactic therapy was observed in 100/143(70%) patients and linked with heart valve disease (OR 8. 95% C.I. 2.43–26.3), venous thrombosis at presentation (OR 2.61 95% C.I. 1.47–4.66), leg ulcers (OR 12.2, 95% C.I. 1.4–107), hypertension (OR 1.99, 95% C.I. 0.92–4.34) and higher aGAPSS (OR 1.08, 95% C.I. 0.99–1.18). Conclusion: In this real life observation, re-thrombosis was common among pAPS patients including in those recommended to receive prophylactic therapy. Different patterns of recurrence were identified and linked with presenting symptoms, specific serological markers, APS-manifestations and comorbidities. Studies that will address interventions to prevent recurrences of APS related events are needed.